The Effectiveness of a New Type of Light Trap in the Fight Against Harmful Insects (Texas Journal of Agriculture and Biological Sciences, 2022)
The article highlights the advantages of a new type of insect trap that provides simultaneous light as well as pheromone and syrupy insect attractants in monitoring and controlling the number of nocturnal pests, especially moths and butterflies. Conventional incandescent coil PRK-4 and BUV insect traps, which have been in practice for many years, are no longer in practice due to their harmful effects on beneficial insects. In our research, it was found that a new type of insect repellant, provided with light, pheromone and syrupy substances that attract insects at the same time, is effective. In particular, it was found that it is clearly distinguished by its harmlessness to entomophages.